Synthesis of Methyl Esters from Banda Nutmeg and Papua Nutmeg Oil Production Wastes Using the Ultrasonication Method - Kapelle, Imanuel Berly Delvis; Sohilait, H.; Rante, Natalia C.D. (Fakultas Teknologi Industri Pertanian, 2024)
Methysters from oil production waste from Banda nutmeg (Myristicafragrans Houtt) and Papuan nutmeg (Myristica Argentea Ware) go through several process stages, namely isolation of trimyristin and synthesis of methyl ester. The process of isolating trimyristin from nutmeg essential oil production waste by maceration using chloroform solvent. The transesterification process with methanol uses a CaO catalyst and ultrasonication method for 20 minutes; the results are analyzed using GCMS. The results of isolating trimyristin from nutmeg oil waste for Papuan nutmeg yielded 55.6 g of trimyristin (22.24%), which was greater than Banda nutmeg which was 49.7 g of trimyristin (19.88%). Transesterification results for Banda nutmeg oil waste obtained 28.57% soakage with a composition of 5 known major methyl ester compounds, namely methyl laurate (3.22%), myristicin (13.48%), metal myristate (53.39%), methyl Palmitate (5.24%), and Methyl Oleate (9.33%). In Papuan nutmeg oil waste, a 3.93% soakage was obtained with a composition of 5 known methyl ester compounds, namely metal myristate (19.80%), methyl arachidate (18.04%), methyl linoleate (1.42%), methyl oleate ( 48.37%), and methyl stearate (3.18%). The sonication method can synthesize methyl esters from nutmeg oil waste and gives different results for the two types of nutmeg. The results of the trimyristin transesterification of Banda nutmeg seeds and Papuan nutmeg seeds using a CaO catalyst using the sonication method resulted in a methyl ester soak of Banda nutmeg waste 28.57% and Papuan nutmeg 3.93%.